FROM SURVIVAL TO SUSTAINABILITY: FINANCIAL PERFORMANCE AND LITERACY EFFECTS IN INDONESIAN SMALL AND MEDIUM-SIZED ENTERPRISES - Retno Fuji Oktaviani; Rachmat Arief; Hakam Ali Niazi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
Tanah Abang Market is the largest fashion hub in Southeast Asia. It faces significant challenges in maintaining business sustainability, particularly for Small and Medium-Sized Enterprises (SMEs) that have experienced severe revenue declines in the post-pandemic era. This study aims to examine the influence of entrepreneurial orientation and risk-taking on business sustainability in Indonesia, with financial performance as a mediating variable and financial literacy as a moderating variable. Therefore, a quantitative approach was employed, using survey data collected from 217 fashion traders, determined using Cochran’s formula. Its data were obtained using a Likert-scale questionnaire (1–5) and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). Furthermore, the findings reveal that entrepreneurial orientation and risk-taking have a significant positive effect on financial performance. Then, the entrepreneurial orientation does not directly affect business sustainability. In contrast, risk-taking directly affects business sustainability. While financial performance plays a crucial mediating role in both relationships, financial literacy significantly strengthens the effect of financial performance on business sustainability. A key novelty of this study is the finding that Tanah Abang traders tend to emphasize survival rather than long-term sustainability strategies.